Evaluation of the larvicidal potential of root and leaf extracts of Saussurea costus (Falc.) Lipsch. against three mosquito vectors:Anopheles stephensi, Aedes aegypti, and Culex quinquefasciatus - Sofi Imtiyaz Ali; Venugopalan Venkatesalu (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: The larvicidal potential of Saussurea costus (Falc.) Lipsch. was studied against the early 4th instar larvae of Anopheles stephensi Liston., Aedes aegypti Linn.,and Culex quinquefasciatus Say. because of the emergence of mosquito resistance to conventional synthetic insecticides. METHODS: At concentrations of 12.5-200 ppm, larvicidal activities were studied under laboratory conditions. RESULTS: After 24 h of exposure, the methanol extract of the roots recorded the highest larvicidal activity against An. stephensi, with LC50 and LC90values of 7.96 and 34.39 ppm, respectively. CONCLUSIONS: We are developing potent larvicidal compound(s) from S. costus for controlling the mosquito larval population.